Conocimiento, actitudes y practicas sobre la mamografía que tienen las mujeres a partir de los 40 años atendidas en el servicio de diagnóstico por imágenes del Hospital Víctor Lazarte Echegaray - Ríos Ramírez, Nelson (2019)
Objective: To determine the level of knowledge, attitudes and practices in relation to mammography performed in women aged 40 and over, who are seen in the diagnostic imaging service of the Víctor Lazarte Echegaray hospital. Materials and Methods: An observational, cross-sectional descriptive study with a quantitative approach, which will be constituted by all patients over 40 years of age who attended the diagnostic imaging service of the Víctor Lazarte Echegaray Hospital, in the month of October 2017, which amounted to a total of 984 clinical histories of the patient users attended. The study will include women patients who have undergone mammography, women over 40 and patients with a family history of cancer. We will apply a survey based on the variables under study which consists of 15 questions that are of the variables knowledge, attitudes and practices of mammography that will be practiced to women who go to the service of diagnostic imaging of the Hospital Víctor Lazarte Echegaray- Trujillo -2018.